Pembatasan dalam Periwayatan Hadis (Taqlil ar-Riwayah) - Oktari Kanus (Program studi Keagamaan Islam, 2022)
This article discusses about the history of the development of hadith that occurred at the beginning of the development of Islam. The traditions that are known today are found in the books of hadith not just by accident, but through a long journey. Starting from the hadith conveyed by the Prophet, then memorized and recorded by the companions, there was even a prohibition from the Prophet himself in recording it, until there was a process where the hadith was arranged in the way it was narrated and finally the hadiths were recorded in a neatly arranged book. The existence of a prohibition on recording this hadith is certainly a problem as to how the hadith will be narrated, the loss of a definite source whether it is true that the hadith comes from the Prophet because there are no notes and reminders about the hadith. However, the restriction in narration (Taqlil ar Riwayah) both from the Prophet himself and from his companions was intended to keep the Qur'an from being mixed with hadith, because at that time the revelation of the Qur'an was taking place.